Fuzzy Evaluation of SWOT Analysis - Meaza Haile; Jiri Krupka (International Journal of Supply Chain Management, 2016)
To develop a strategy for an organization it is important to understand the organization and its surrounding environment. Strength, Weakness, Opportunity, Threat (SWOT) analysis is a famous tool to perform this task precisely by showing the strength, weakness of the organization and the external factors, opportunities and threats that affect its success. The SWOT analysis is commonly used by business; however, non-profit organizations also use the SWOT analysis for decision-making and strategy evaluation. The limitation of SWOT analysis is it does not give weight for the factors and there is no quantified result from the analysis. The methods introduced in this paper are Sugeno lambda measure and Choquet fuzzy integral. Sugeno lambda measure is used for aggregating the importance of characteristics and Choquet fuzzy integral is used for the overall analytical evaluation of strength, weakness, opportunity and threat of a specific organization. A case study has been conducted for a currency exchange office and the region of Pardubice, Czech Republic (CR) to explain the application of the proposed approach for profit and non- profit organizations.